Effect of Time-Temperature Abuse on Microbiological and Physiochemical Properties of Barramundi (Lates Calcarifer, Bloch) Fillets - Younus Zakhariya, Sona; Fotedar, Ravi; Prangnell, D. (Wiley-Blackwell Publishing, Inc., 2015)
The effect of time-temperature abuse on quality and shelf life of barramundi (Lates calcarifer) fillets using microbiological and physiochemical tools was investigated. Fillets were subjected to three different pre-blast freezing (PBF) temperatures viz. 5, 0 and -20C for 0 h, 1 h, 1, 2, 4, 8 and 16 days, after which fillets were exposed to -80C for 8 h and then stored at -20C for 20 days. Color and rheological parameter values changed as PBF time period progressed at each temperature tested. There was minimal change to the microbiological and physiochemical properties of fillets stored at -20C from 0 h to 16 days. Total viable count, total volatile base nitrogen, pH, protein, color and rheological parameters of fillets that underwent PBF temperature period at 0 and 5C for 16 days deteriorated significantly compared with those treated at -20C. The shelf life of PBF barramundi fillets at 0 and 5C was 8 days.